EFFORTS AND OBSTACLES FACED IN PROVIDING LEGAL PROTECTION TO CHILDREN AS VICTIMS OF DOMESTIC VIOLENCE IN LAU GUMBA BERASTAGI VILLAGE - Sahlepi, Mhd Arif; Tumiran, Tumiran; Rangkuti, Charles; Ardani, Syafira (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine the implementation of legal protection for children as victims of domestic violence in Lau Gumba Village and to determine the obstacles faced in providing protection for children as victims of domestic violence. This research was conducted at the Berastagi District Police and the Berastagi District Prosecutor's Office using technical observation or direct observation and interviews, namely by communicating directly through interviews with several Berastagi District Police legal officers and other informants as well as distributing questionnaires to prosecutors at the Berastagi District Prosecutor's Office. In relation to the legal protection of children which has been stipulated in Law Number 23 of 2002 and Law Number 13 of 2006 concerning the protection of witnesses and victims which is the basis of the 1945 Constitution of the Republic of Indonesia as a rule that guarantees legal protection for children who are victims of violence in the home ladder. The author will provide an overview of the form of legal protection for children who are victims of domestic violence in Lu Gumba Village which is not yet optimal from the perspective of Law Number 23 of 2002 in conjunction with Law Number 35 of 2014. The obstacles faced in provide legal protection for children as victims of domestic violence, namely: traditional constraints, psychological constraints of children and the constraints of ignorance of the children themselves and society. As well as several obstacles faced by law enforcement officers.